The improvement of rice straw quality by urea-molasses treatment - Manurung, Tambak; Zulbardi, Muhammad (Indonesian Journal of Animal and Veterinary Sciences, 1996)
A study was conducted in Balai Penelitian Temak Bogor to evaluate the effect of urea-molasses treatment on the quality of rice straw . Five levels of urea were 0%, 0.5%, 1%, 1 .5% and 2% and 4 levels of molasses were 0%, I%, 2% and 3%. The study was conducted based on factorial completely randomized design with 3 replications . Urea and molasses were mixed with 5 kg chopped rice straw and stored for 21 days in plastic bag . Parameters observed were dry matter, organic matter, crude protein, crude fibre, and silica contents . Nutritive value of rice straw was measured by proximate analysis and its nutrient digestibility by in-vitro using rumen liquid of fistulated Ongole-crossed cattle . The results showed that urea and molasses treatment on rice straw decreased the dry matter and silica contents but increased the crude protein content of rice straw (P<0 .01). Dry matter and organic matter digestibility of rice straw didnt show the significant different among urea treatment but highly significant increased (P<0.01) by the molasses treatment. It was concluded that urea and molasses treatment on rice straw could improve the quality so that by the levels of 1 .5% urea and 3% molasses produced the similar quality with napier grass . Â  Key words: Rice straw, urea, molasses,nutritive value